Athlete-reported outcome measures for monitoring training responses: A systematic review of risk of bias and measurement property quality according to the COSMIN guidelines - Jeffries, A. C.; Wallace, L.; Coutts, A. J.; McLaren, S. J.; McCall, A.; Impellizzeri, F. M. (International Journal of Sports Physiology and Performance, 2020)
Background: Athlete-reported outcome measures (AROMs) are frequently used in research and practice but no studies have examined their psychometric properties. Objectives: Part 1—identify the most commonly used AROMs in sport for monitoring training responses; part 2—assess risk of bias, measurement properties, and level of evidence, based on the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines. Study Appraisal and Synthesis Methods: Methodological quality of the studies, quality of measurement properties, and level of evidence were determined using the COSMIN checklist and criteria. Results: Part 1—from 9446 articles screened for title and abstract, 310 out of 334 full texts were included; 53.9% of the AROMs contained multiple items, while 46.1% contained single items. Part 2—from 1895 articles screened for title and abstract, 71 were selected. Most measurement properties of multiple-item AROMs were adequate, but content validity and measurement error were inadequate. With the exclusion of 2 studies examining reliability and responsiveness, no validity studies were found for single items. Conclusions: The measurement properties of multiple-item AROMs derived from psychometrics were acceptable (with the exclusion of content validity and measurement error). The single-item AROMs most frequently used in sport science have not been validated. Additionally, nonvalidated modified versions of the originally nonvalidated items are common. Until proper validation studies are completed, all conclusions based on these AROMs are questionable. Established reference methods, such as those of clinimetrics, should be used to develop and assess the validity of AROMs.